Visualizing the Growth of Green Retailing: A Bibliometric Mapping of Sustainable Practices in Retail Marketing - Judijanto, Loso; Arini, Rani Eka; Pahrijal, Rival (West Science Social and Humanities Studies, 2025)
This study presents a bibliometric analysis of the academic literature on green retailing and sustainable practices in retail marketing, using data retrieved from the Scopus database (2000–2024). Employing VOSviewer for co-authorship, citation, and keyword co-occurrence analysis, the study identifies core research themes, influential contributors, and evolving trends in the field. The results reveal that “green retailing,” “green marketing,” and “cost optimization” are central to the scholarly discourse, reflecting the growing strategic importance of sustainability in retail operations. The analysis also uncovers a temporal shift from foundational environmental themes to more actionable managerial strategies. India stands out as a hub of international collaboration, and author network analysis highlights prominent research clusters around figures such as Sarkis J. and Lai K.H. While the literature has matured in linking green practices with business outcomes, emerging gaps include social dimensions of sustainability and digital transformation in retail. The study concludes with recommendations for future research directions that emphasize interdisciplinary inquiry and practical application in advancing sustainable retail marketing.